Adsorption and reduction of Cr(VI) by a novel nanoscale FeS/chitosan/biochar composite from aqueous solution. Issue 4 (August 2021) - Yang, Yan; Zhang, Yuhao; Wang, Guiyin; Yang, Zhanbiao; Xian, Junren; Yang, Yuanxiang; Li, Ting; Pu, Yulin; Jia, Yongxia; Li, Yun; Cheng, Zhang; Zhang, Shirong; et al.
Abstract: The purpose of this study was to synthesize FeS/chitosan/biochar composite (FSBC) to remove Cr(VI). Results indicate that the modification of FeS particles and chitosan to biochar provided large specific surface area and more active adsorption sites. FSBC(1:1:1) have an enhanced Cr(VI) adsorption capacity of 103.93 mg g-1 at 0.01 g per 50 mL Cr(VI) solution compared with 19.97 mg g−1 for FeS particles and 22.45 mg g−1 for biochar. Increasing temperature promote Cr(VI) removal. By contrast, increasing Cl- and SO42- concentrates and solution pH prevented Cr(VI) adsorption. Cr(VI) removal could attribute to surface adsorption, reduction and precipitation. XPS results indicated that 76.07% of Cr(VI) removal was due to reduction or precipitation, and 23.93% could be ascribed to surface adsorption. After adsorption-desorption cycle, Cr(VI) removal capacities are 70.42, 65.33 and 11.67 mg g−1 for FSBC(1:1:1), FSBC(1:1:5) and FSBC(5:5:1), respectively. The study demonstrated that FSBC were high-effective adsorbents for Cr(VI) removal in the water environment. Graphical Abstract: ga1 Highlights: FSBC was synthesized combining the advantages of biochar, chiostan, and FeS. FSBC(1:1:1) has an enhanced Cr(VI) removal capacity of 103.93 mg g −1 . Cr(VI) removal could attribute to surface adsorption, reduction and precipitation.